The Impact of Organizational Culture, Leadership, and Organizational Citizenship Behavior on Employee Performance in The Tourism Industry in Jakarta - Moeins, Anoesyirwan; Vikki Subroto, Victor; Marhalinda, Marhalinda (Green Publisher, 2024)
This study investigates the impact of organizational culture, leadership styles, and organizational citizenship behavior (OCB) on employee performance within the tourism industry in Jakarta. As one of Indonesia's key economic sectors, understanding these dynamics is crucial for enhancing employee productivity and job satisfaction. The research employs a mixed-method approach, utilizing quantitative surveys to measure relationships between the variables and qualitative interviews to gain deeper insights into employee experiences. Findings indicate that a strong organizational culture and effective leadership significantly promote OCB, which in turn enhances employee performance. This study provides valuable implications for management practices in the tourism sector, highlighting the need to foster a supportive work environment that encourages proactive employee engagement.